ROLE-PLAYING METHODS IN SECOND LANGUAGE LEARNING - Widiasri, Dewa Ayu; Dwi Payanti, Dewa Ayu Karina (JURNAL EDUSCIENCE, 2024)
This article describes the activities that can be carried out during the application of the role-playing method in teaching a second language. The theory used is Stephen Krashen's second language learning theory. This research is a literature study research. The results of this study describe the activities that can be carried out during the application of the role playing method, namely by listening to a short dialogue and then playing a role. Second, reading storybooks in the target language and then choosing important events in the story to act out. The use of this role-playing game provides a great opportunity for learners to communicate even though they have limited second language vocabulary. Therefore, role-playing encourages students to be brave in communicating, so that it will be easier to understand the second language they are learning. Teachers can use this method in teaching a second language.